# How do you solve #x(x+6)=-2# using the quadratic formula?

OR

Putting it in formal format:

Or

By signing up, you agree to our Terms of Service and Privacy Policy

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (x(x+6)=-2) using the quadratic formula, first, express the equation in the standard form (ax^2 + bx + c = 0). In this case, (a = 1), (b = 6), and (c = 2). Then, substitute these values into the quadratic formula: (x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}}). After substituting the values, solve for (x) by performing the arithmetic operations indicated.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you solve # x^2 - 2x + 4# using the quadratic formula?
- How do you graph the parabola #(x+2)^2=-8(y-1)# using vertex, intercepts and additional points?
- How do you solve #x^3 - 10x^2 +24x = 0 #?
- What is the solution set for #3x^5-48x=0#?
- Susan is making and selling earrings. Her weekly cost for advertising is $36, and each pair of earrings cost $1.50 to produce. If Susan sells the earrings at $6 per pair, how many pairs must she sell to break even?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7